2017
DOI: 10.3390/resources6030031
|View full text |Cite
|
Sign up to set email alerts
|

Market Feasibility of Faecal Sludge and Municipal Solid Waste-Based Compost as Measured by Farmers’ Willingness-to-Pay for Product Attributes: Evidence from Kampala, Uganda

Abstract: There is a great potential to close the nutrient recycling loop, support a 'circular economy' and improve cost recovery within the waste sector and to create viable businesses via the conversion of waste to organic fertilizers. Successful commercialization of waste-based organic fertilizer businesses however largely depends on a sound market. We used a choice experiment to estimate farmers' willingness-to-pay (WTP) for faecal sludge and municipal solid waste-based (FSM) compost in Kampala, Uganda and considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…The faecal coliform log10 numbers are higher than those considered acceptable levels in Canada [38] or the USA [39], where standards stipulate faecal coliforms <1000 CFU g−1 (= 3 as Log10 numbers). We, anyhow, did not further analyse if the colonies found belonged to Escherichia coli or to some other species.…”
Section: Hygienic Quality Of Lettuces and Their Tastementioning
confidence: 80%
See 1 more Smart Citation
“…The faecal coliform log10 numbers are higher than those considered acceptable levels in Canada [38] or the USA [39], where standards stipulate faecal coliforms <1000 CFU g−1 (= 3 as Log10 numbers). We, anyhow, did not further analyse if the colonies found belonged to Escherichia coli or to some other species.…”
Section: Hygienic Quality Of Lettuces and Their Tastementioning
confidence: 80%
“…Furthermore, waste-based fertilizer could allow for poor farmers a possibility to save money since mineral fertilizers have high prices. Faecal sludge-based fertilizer could be commercialized as it has been successfully done in Uganda [38] and in Haiti and Kenya [39]. In these areas, farmers are willing to pay a reasonable price for these fertilizers and they can then sell their yields.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, waste-based fertilizer could allow poor farmers a possibility to save money, since mineral fertilizers have high prices. Faecal sludge-based fertilizer could be commercialized as it has been successfully done in Uganda [40] and in Haiti and Kenya [41]. In these areas, farmers are willing to pay a reasonable price for these fertilizers, and they can then sell their yields.…”
Section: Discussionmentioning
confidence: 99%
“…Modifying the properties of the final product can also have significant effects on its profitability. Danso et al [30] showed the potential effect of modifying compost attributes in Uganda: farmers' willingness to pay was US$0.40 more if the fertilizer was certified, which gave an overall price 67 times higher than the cost of providing it. If the compost was pelletized, they would be willing to pay $0.127 more, but this meant the sale price was less than the price required to produce the compost.…”
Section: Challenges To Profitabilitymentioning
confidence: 99%
“…Certification could be beneficial for improving commercialization of human excreata derived fertiliser, potentially increasing its market value [30]. The value in creating certifications and standards for sanitation is recognized, with several ISO standard-setting processes currently under way.…”
Section: Certification To Increase Product Credibility and Valuementioning
confidence: 99%